SELECTION OF FOREIGN DESTINATION TOURISM USING THE MULTI ATTRIBUTE RATTING SIMPLE METHOD (International Journal of Psychosocial Rehabilitation, 2020)
The trend of traveling is young people; now many are going abroad. Although only tourist destinations around Asia, they take advantage of cheap flight tickets. Data revealed that during 2018, more than 50 percent had traveled twice in 1-4 days. These findings indicate that they prefer short but frequent trips. Search results are known if many young Indonesians have tourist destinations in the majority of countries in the Asia Pacific region, and those countries include Singapore, Malaysia, South Korea, Australia, Thailand, China, and Japan. This research was conducted to provide recommendations for domestic tourists to provide recommendations for decision-making to choose the destination country. Decision-making using the SMART (Simple Multi Attribute Rating Technique) method is a multi-attribute decision-making technique in choosing several alternatives. There are several reasons that make many people choose to vacation abroad, namely: facilities, prices, pride, experience,e, and atmosphere. The research data were obtained by interviewing 100 people. The results of the data are processed using the SMART method and get the following ratings: xxx. It is hoped that this research can provide recommendations for tourists to choose shipping expeditions and for travel service providers to make plans that can increase income.